Students' Perceptions On An Exemplary Speaking Lecturer - fathorrohim Fathorrohim (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
The students’ hardship in speaking skill due to several problems appear in this paper as the following; limited of pronunciation and vocabulary, unconfident, unsuitable facilitator. This study was an attempt to describe how becoming an exemplary speaking lecturer according to students’ perception. Meanwhile, the current study applies survey design as descriptive quantitative approach. Forty-eight English department students from different level of semester (henceforth, participants) were recruited by means of convenience sampling technique. They were asked to fill out a set of questionnaires as main instrument of this study. The results of this study yielded that the participants’ belief being an exemplary speaking lecturer were seen complex. It is proven from the instrument that break down as three main of frameworks of this study; pedagogic enactment, teacher teaching method and personality traits. In pedagogic enactment category, 80 % respondents much strongly proposed that group discussion regard as the most priority in classroom system to require teaching goal of ESL. Then, the aspect that covered teacher teaching method “ESL prefer giving task rather than come to the class” did not served as the ESLs’ feature in this research by 47 % of students. Presentation method was the most favorite criteria needed by mostly respondents 86 % of this category. Thus, the personality traits of English speaking teacher demanded by strongly 85 % this participants were the teacher who is aware toward students’ needs and not difficult to socialize with students about certain topic in speaking course.